Deriving indicators of soil degradation from soil aggregation studies in southeastern Spain and southern France (Geomorphology, 1998)
Soil degradation is perceived as a major threat in the Mediterranean region due to changes in land-use and possible future climate change. Soil aggregation parameters are used here to demonstrate their potential as a key-indicator for land degradation studies. The monitoring of these indicators offers a means of establishing the vulnerability and resilience of geo-ecosystems. Soil aggregation stability and distribution were studied on soils with an open shrubby vegetation cover, from several places in southeastern Spain and southern France, by applying drop tests and determining aggregate size distributions. Aspect and vegetation cover were incorporated in the soil sampling. Several indices were derived from these analyses to indicate the degree of soil aggregation. This was done by referencing to a base level of aggregation bare soil aggregation . It was found that soil aggregates were more stable and were often coarser under vegetation, when compared to . their immediate surrounding bare areas. A similar, slightly less clear effect was noted on N-facing exposed slopes when compared to S-facing exposed slopes. Long-term changes were found by studying cultivated land, abandoned fields and land covered by semi-natural vegetation, on comparable substrate and comparable land units. It is clear that soil aggregation and aggregate stability increases with time years . It is argued that soil aggregation indices can be used as a key-indicator for . degradation processes at a fine scale with implications for runoff and sediment generating processes at the hillslope scale